Tired ladies take a stand : a novel [large type] - Anthony, Gretchen (Thorndike Press large print top shelf, 2024)
"During one unforgettable year in their twenties, best friends Emma, Fern, Carolina, and Andi make a pact to embrace whatever life throws at them, inspiring Fern to write a memoir detailing their escapades and the magical power of saying Yes. But fast forward twenty years and they have reached their bandwidth of responsibilities. Fern is a full-time writer struggling to pay the bills. Carolina is a fitness-obsessed workaholic. Andi is a disillusioned human rights lawyer. And Emma is a stressed-out divorcée in the thick of planning her daughter's wedding. To reconnect to the fun, fulfilled women they were before, they must learn how to stop saying Yes to everything asked of them. And so begins the Year of No"--